A network approach to analysis of the performance of milk traders, producers and BDS providers in Tanzania and Uganda - Baker, Derek; Omore, Amos O.; Guillemois, D.; Mtimet, Nadhem (2013)
Network analysis is applied to an investigation of the effectiveness of pro-poor interventions in the dairy industry of Tanzania and Uganda. A sample of milk producers and traders, and of suppliers of Business Development Services, is constructed by a snowball method to preserve market and other linkages amongst the actors. Geometric analysis of the resulting networks is used for simple network diagnostics which are then applied to market structure analogues. Statistical and econometric analysis is then applied to examining actors’ characteristics and performance by way of conventional actor-specific variables and by using information about the links between actors within networks. Indications of the success of the Business Development Services support programme are derived from network characteristics.